Writing measures and outcomes in CLIL and EMI. (15th August 2021) - Graham, Keith M.; Eslami, Zohreh R.
Abstract : This study utilizes a systematic review approach to examine current research in content and language integrated learning (CLIL) and English-medium instruction (EMI). Studies were examined for their use of language-related and content-related writing measurement and outcomes. Findings on CLIL/EMI writing measurement shows that studies have utilized a variety of methods for measuring language, but measurement of the content dimension is limited. While some studies in the review combine multiple types of writing measures, CLIL writing research often does not simultaneously assess both the language and content dimensions of writing. For writing outcomes, the reviewed studies show CLIL/EMI generally equals or exceeds traditional language classrooms and that CLIL/EMI instruction leads toward growth in some but not all (i.e. accuracy), language-related metrics. However, regarding the content dimension, the findings are mixed and show CLIL/EMI writing generally does not communicate disciplinary content knowledge appropriately. It is recommended that future research gives more attention to measuring both the language and content dimensions of writing while also incorporating new methods for measuring discipline-specific content in writing. It is also recommended that instructors increase their language awareness and reconsider how disciplinary writing is taught in their CLIL/EMI classroom.